Pengaruh Word of Mouth dan Brand Image terhadap Keputusan Pembelian Produk MS Glow - Pebrianti, Vera; Yulia, Iis Anisa; Fitrianti, Dewi (Jurnal EMT KITA, 2026)
This study aims to determine the influence of word of mouth and brand image on purchasing decisions for MS Glow products. This research is a quantitative and causal associative study. Data collection in this study was obtained from a survey using a questionnaire technique to MS Glow consumers. The data analysis technique used is Multiple Linear Regression. The results of the study indicate that partially word of mouth and brand image have a positive influence on purchasing decisions. Simultaneously, word of mouth and brand image together influence purchasing decisions.